2012
DOI: 10.5665/sleep.1998
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Disorganization of Circadian Rhythmicity and Sleep-Wake Regulation in Mechanically Ventilated Patients Receiving Continuous Intravenous Sedation

Abstract: The circadian rhythms and PSG of patients receiving mechanical ventilation and intravenous sedation exhibit pronounced temporal disorganization. The finding that most subjects exhibited preserved, but phase delayed, excretion of aMT6s suggests that the circadian pacemaker of such patients may be free-running.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
108
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 57 publications
8
108
0
7
Order By: Relevance
“…43,[70][71][72] Similarities between sleep and sedation include reduced responsiveness, reduced muscle tone, respiratory depression, and temperature deregulation. 49,50 However, sleep and sedation differ markedly. Sleep is a natural and essential biological process, with cyclical sleep architecture contributing to physiological restoration, whereas sedation is not natural and does not support normal sleep patterns.…”
Section: Reviewing the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…43,[70][71][72] Similarities between sleep and sedation include reduced responsiveness, reduced muscle tone, respiratory depression, and temperature deregulation. 49,50 However, sleep and sedation differ markedly. Sleep is a natural and essential biological process, with cyclical sleep architecture contributing to physiological restoration, whereas sedation is not natural and does not support normal sleep patterns.…”
Section: Reviewing the Evidencementioning
confidence: 99%
“…Limitations in the use of sleep assessment technology and communication challenges with critically ill patients contribute to the difficulty of measuring sleep in ICU patients. 49 What is known about sleep is that patients in the ICU have fragmented sleep, often experiencing multiple sleep-wake cycles that fail to reach N3 or restorative REM stage sleep. 43,44,50,51 The connection between sleep deprivation and delirium has particular importance in the ICU practice environment.…”
Section: Reviewing the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In children with critical illness, sleep may play an even more important role in recovery. 3 Several studies [4][5][6] have indicated that both adult and pediatric ICU patients experience disturbances in circadian rhythm and decreases in slow-wave sleep. Although critically ill patients have multiple risk factors for sleep fragmentation, the most modifiable is the external environment, because sound and light levels play a key role in sleep-wake homeostasis.…”
mentioning
confidence: 99%
“…Although critically ill patients have multiple risk factors for sleep fragmentation, the most modifiable is the external environment, because sound and light levels play a key role in sleep-wake homeostasis. 2,[4][5][6][7] Disturbances in sleep continuity may be associated with an increased risk for delirium in patients admitted to the ICU. [8][9][10][11] Critical illness implies the need for invasive medical instrumentation and frequent interruptions for nursing care and monitoring.…”
mentioning
confidence: 99%